Citywide Inclusive Sanitation Through Scheduled Desludging Services: Emerging Experience From India - Mehta, Meera; Mehta, Dinesh; Yadav, Upasana (Frontiers in Environmental Science, 2019)
The focus of Swachh Bharat Mission (Clean India Mission) was to build toilets to make India open defecation free. While India has succeeded in achieving this goal, to move towards “safely managed sanitation” as per target 6.2 of the Sustainable Development Goals, it is necessary to ensure that all fecal waste is safely collected and treated. The common practice for desludging of septic tanks is ‘demand-based desludging’ rather than a regular service. Such practices have adverse social and environmental impacts. To overcome these shortcomings, scheduled desludging is advocated. This paper first reviews the need for regular desludging of septic tanks. It then outlines the emerging experience of design and implementation of scheduled desludging for inclusive, equitable, and sustainable sanitation to achieve social and environmental benefits in two Indian cities. In these cities, a performance-linked annuity payment framework is used to engage a private desludging enterprise. Payment is met through a sanitation tax and transfer from the general property taxes. It outlines the benefits of scheduled desludging in Indian cities and argues that it is critical to achieve improved sanitation.